Проблема грамматических трансформаций перевода в полиязычных группах вузов - Абдрахман, Г.К.; Жумабаева, А.М. (My University, 2016)
In article grammatical transformations of transfer of the Kazakh, Russian and English languages are considered in the comparative plan. Grammatical categories and forms of English, Kazakh and Russian languages are compared.
Keywords: transfer; machine translation; grammatical transformations